Factors Affecting The Loyalty of Commuter Line Train Users - Makky, Muhammad Nabil; Hartoyo; Krisnatuti, Diah (Business Review and Case Studies, 2025)
Background: In the development of business, Indonesia's commuter line is widely rumored to have service quality that is still below customer expectations. Today's consumers are more critical and undetectable of criticism that will appear on social media. The fading of customer trust and loyalty is an important issue for commuter line managers. Purpose: This study aims to identify the characteristics and behavior of commuter line users, analyze service quality, relational marketing, and customer satisfaction on commuter line user loyalty, and formulate managerial implications for increasing commuter line train user loyalty. Methodology/approach: This study uses the top two boxes analysis method and Structural Equation Model - Partial Least Square (SEM-PLS) analysis with convenience sampling 140 respondents in the Greater Jakarta area.Findings/Result: The results showed that service quality and relational marketing affect customer satisfaction and thus have an impact on customer loyalty. To increase customer loyalty, PT KCI should maintain customer trust as one of the relational marketing efforts by committing to providing updates on developments, travel disruptions, accidents, or changes to departure schedules on official platforms (KAI Access) and social media.Conclusion: that service quality and relational marketing affect customer satisfaction and thus have an impact on customer loyalty.Keywords: service quality, relational marketing, customer satisfaction, customer loyalty, commuter line